Regeneration of the Dry Peninsular Sal Forests of West Bengal - Chaudhuri, K. N. (Indian Forester, 1958)
The A3 - Dry Peninsular Sal forests of West Bengal cover an area of about 1,600 sq. miles in the western districts south of the Ganges. Potentially, these forests are very valuable because of their proximity to Calcutta and Industrial areas and the good network of communications that serve them. But unfortunately the forests have mostly been reduced to coppiced sal in various stages of deterioration and erosion as a result of prolonged mal-treatment by man. The influence of adverse biotic factors has been analysed in some detail. The ecological status of the forest is discussed and its bearing on the problem of natural regeneration is emphasized. As regards natural regeneration by seedlings several instances are cited to indicate that an increase in the rotation of coppice, complete protection against adverse biotic factors, viz., grazing, burning and indiscriminate felling, and soil conservation measures inside the forests, would go a long way to induce natural regeneration. The single uncontrollable variable, viz., the time lag between the seeding of sal and the onset of the monsoon, however, is likely to necessitate the adoption of a rather long establishment period. The importance of patient research with a view to obtain fundamental or basic knowledge on the ecology of sal is emphasized, and the lines on which investigations should be directed are also indicated. Systematic and long-term research is being initiated for tackling the problem of natural regeneration; meanwhile the trial and error efforts of eight years seem to have yielded a fairly reliable technique for artificial regeneration of sal in the districts of Midnapore, Bankura, Burdwan and Birbhum. The technique has been descr,bed in brief and a reference has been made to the West Bengal Forest Bulletin NO.5, which deals with the matter in detail. Constant endeavour is, however, being made to perfect the technique.